(untitled) (Hematology Meeting Reports, 2009)
The combination of rituximab plus CHOP (R-CHOP) has dramatically changed the outcome of patients with diffuse large B-cell lymphoma but there are still eras where the results obtained with RCHOP chemotherapy are not so satisfying. If R-CHOP is associated with 5-year progression-free survival (PFS) and overall survival (OS) of 70% and 80%, respectively, in patients with good risk presentation (IPI score